THE ROLE OF BOOKS IN THE LIFE OF YOUNG GENERATION - Rasulova, Zuhra (Журнал иностранных языков и лингвистики, 2021)
There is no doubt that the people of the Republic of Uzbekistan have expressed their dissatisfaction with the importance of the mutually beneficial and effective influence of the people of our people, the greatness of the people, the greatness of the people, the lifestyle of the deceased, the fate of the deceased.